2006
DOI: 10.1021/jf058166c
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Glyphosate Mode of Action in Nodular Metabolism:  Role of Shikimate Accumulation

Abstract: The short-term effects of the herbicide glyphosate (1.25-10 mM) on the growth, nitrogen fixation, carbohydrate metabolism, and shikimate pathway were investigated in leaves and nodules of nodulated lupine plants. All glyphosate treatments decreased nitrogenase activity rapidly (24 h) after application, even at the lowest and sublethal dose used (1.25 mM). This early effect on nitrogenase could not be related to either damage to nitrogenase components (I and II) or limitation of carbohydrates supplied by the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 31 publications
4
79
1
8
Order By: Relevance
“…Outra causa poderia ser um menor aporte de nitrogênio via fixação biológica, que pode ser afetado por aplicações com glyphosate (Zablotowicz & Reddy, 2004;María et al, 2006;Santos et al, 2007a,b;Dvoranen et al, 2008;Zobiole et al, 2010a).…”
Section: Resultsunclassified
“…Outra causa poderia ser um menor aporte de nitrogênio via fixação biológica, que pode ser afetado por aplicações com glyphosate (Zablotowicz & Reddy, 2004;María et al, 2006;Santos et al, 2007a,b;Dvoranen et al, 2008;Zobiole et al, 2010a).…”
Section: Resultsunclassified
“…In addition, it was observed that not only was nitrogenase activity decreased rapidly in Bradyrhizobium sp. (Lupinus) bacteroids but also the amount of the two nitrogenase components (Mo-Fe protein and Fe protein) diminished after glyphosate application (10).…”
mentioning
confidence: 96%
“…In addition, it has also been shown that the antimicrobial properties of glyphosate are not only due to EPSP inhibition, as mentioned previously, but also to the high concentrations of shikimic acid and protocatechuate that it causes [18,19]. These important features have encouraged diverse research groups to study in detail the substrate binding requirements of this enzyme [20][21][22][23][24][25].…”
Section: Targeting Shikimate Kinasementioning
confidence: 84%
“…The MD simulation studies carried out with (6R)-6-hydroxyshikimic acid (18) showed that this compound caused significant changes in the water network and caused an opening of the SB domain by nearly 6 Å. During the simulation the ligand also undergoes a conformational change to the thermodynamically more stable conformation, i.e., with C4 and C5 hydroxyl groups in the pseudo-equatorial conformation.…”
Section: Fig (2) Competitive Reversible Inhibitors Of Mt-skmentioning
confidence: 99%